Potential of Bacillus stercoris B.PNR2 to stimulate growth of rice and waxy corn under atrazine-contaminated soil - Somtrakoon, Khanitta; Prasertsom, Preamkamon; Sangdee, Aphidech; Pengproh, Rattana; Chouychai, Waraporn (Journal of Aridland Agriculture, 2024)
The presence of atrazine residue in agricultural soil may affect crop growth and the activity of plant growth-promoting bacteria. Therefore, this study investigated the impact of atrazine contamination on indole-3-acetic acid (IAA) production by Bacillus stercoris B.PNR2. Subsequently, the ability of B. stercoris B.PNR2 to stimulate the seedling growth of rice cultivars RD6 and Leum Pua, as well as the waxy corn cultivar Muang Tam, under atrazine contamination, was determined. The results showed that B. stercoris B.PNR2 produced IAA under various atrazine concentrations, and atrazine was not toxic to B. stercoris B.PNR2 cells. Atrazine at 20 mg/kg of soil did not affect the shoot and root dry weight of rice cultivars RD6 and Leum Pua, as well as the waxy corn cultivar Muang Tam grown in atrazine-contaminated soil without receiving a bacterial inoculum. The application of B. stercoris B.PNR2 did not stimulate the germination and growth of any of the plants used in this study. The application of B. stercoris B.PNR2 decreased the shoot and root dry weight of waxy corn grown under atrazine-contaminated soil. Additionally, the chlorophyll b and total chlorophyll content in rice cultivar RD6, grown under atrazine-contaminated soil, decreased to only 162.6 ± 4.2 and 616.0 ± 55.8 μg/g fresh weight, which was related to the increase in proline content to 343.6 ± 41.6 μg/g fresh weight. In conclusion, it can be stated that soaking seeds with B. stercoris B.PNR2 was not an appropriate means of inoculation to stimulate the growth of plants in this study.